2011
DOI: 10.1111/j.1745-6592.2011.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Contaminants at a Closed and an Operating Landfill in Oklahoma

Abstract: Landfills are the final depositories for a wide range of solid waste from both residential and commercial sources, and therefore have the potential to produce leachate containing many organic compounds found in consumer products such as pharmaceuticals, plasticizers, disinfectants, cleaning agents, fire retardants, flavorings, and preservatives, known as emerging contaminants (ECs). Landfill leachate was sampled from landfill cells of three different age ranges from two landfills in Central Oklahoma. Samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 27 publications
1
39
1
Order By: Relevance
“…The concentrations of DEET in Sites A and B leachate were higher than the highest calibration standard and are reported as greater than the highest calibration standard. The concentration of DEET was higher than previously reported in studies of U.S. landfill leachates (n = 5; range <80-8100 ng L À1 ) (Barnes et al, 2004;Masoner et al, 2014) but lower than a second study (43.7-52.8 mg L À1 ) (Andrews et al, 2012). The concentration of DEET has been reported in a range of surface water samples from the U.S. and the concentration is typically in ng L À1 ranges ( Weigel et al (2004) is also typically lower than was found in the samples analyzed in this study but wastewater volumes are considerably higher.…”
Section: Levels Of Contaminantscontrasting
confidence: 71%
See 3 more Smart Citations
“…The concentrations of DEET in Sites A and B leachate were higher than the highest calibration standard and are reported as greater than the highest calibration standard. The concentration of DEET was higher than previously reported in studies of U.S. landfill leachates (n = 5; range <80-8100 ng L À1 ) (Barnes et al, 2004;Masoner et al, 2014) but lower than a second study (43.7-52.8 mg L À1 ) (Andrews et al, 2012). The concentration of DEET has been reported in a range of surface water samples from the U.S. and the concentration is typically in ng L À1 ranges ( Weigel et al (2004) is also typically lower than was found in the samples analyzed in this study but wastewater volumes are considerably higher.…”
Section: Levels Of Contaminantscontrasting
confidence: 71%
“…In another landfill leachate study, fluoxetine was also less than the detection limit (Andrews et al, 2012). However, the lack of detection of fluoxetine is consistent with reports of low frequency of detection of fluoxetine in surface waters Glassmeyer et al, 2005;Benotti et al, 2009), groundwaters (Barnes et al, 2008) and wastewaters (Weigel et al, 2004).…”
Section: Levels Of Contaminantsmentioning
confidence: 57%
See 2 more Smart Citations
“…In leachate samples, the detection of pharmaceuticals has never been studied except few reported papers [9,10]. Landfills may be sources of a large number of organic compounds known as emerging contaminants (ECs and/or EDCs) such as pharmaceuticals, pesticides, fertilizers and others.…”
Section: Introductionmentioning
confidence: 99%